Methodological foundations of distributed computer network synthesis of offices - Нефедов, Леонид Иванович; Шевченко, Мария Валериевна; Биньковская, Анжела Борисовна; Петренко, Юрий Антонович (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the structural models of information technology and informative-reference providing are developed, and also the substantiation of multi-objective optimization models are carried out, depending on the degree of uncertainty of initial information for the synthesis of the distributed computer network of the system of offices